The Evolution of Authorship: Work Made by Code - Birdy, Annemarie (The Columbia Journal of Law & the Arts, 2016)
While it’s true that robots don’t yet run the world, computer systems dedicated to particular tasks have continued to get smarter and more independent over time. Some of these systems are designed to produce works that fall under the rubric of algorithmic or generative art. Practitioners of generative art take a systemsapproach to artistic production, removing their own personalities from the creative process and ceding control to self-executing algorithms. Often, these artists employ computers to run their algorithms, but sometimes they don’t. Sometimes they compose algorithmically by hand, challenging traditional constructs of artistic inspiration by highlighting the rule-bound nature of human creativity. As Anne Balsamo has pointed out, the term “computer” was originally coined to describe human beings, an irony that many of us don’t appreciate.12 The first “computers” were actually female clerical workers who operated mechanical adding machines. In the realm of popular culture, procedural generation techniques are being used more and more in the design of computer games.13 These techniques promise the development of the endless game, where the user never runs out of levels to complete or terrain to explore because the game itself is generating new content as it’s being played. In the generative art domain, an AI program called AARON provides a good basis for discussing the problems and possibilities associated with computer authorship. AARON’s underlying code was written by Harold Cohen beginning in 1973. Cohen, an art professor at the University of California, San Diego, spent the next thirty years of his career refining AARON’s code and basically “teaching” AARON about color, representation, and form.14 AARON’s works, which are generated autonomously by Cohen’s program, have been exhibited in galleries around the world and are on permanent display at the Computer [History] Museum in Boston.15 As Cohen revised AARON’s code over time, AARON’s output evolved stylistically from representation to abstraction— the type of developmental arc that one might expect of a human artist. Indeed, it was Cohen, through AARON’s changing code, who redefined the outer bounds of AARON’s artistic capacity. There’s certainly no question that